Readiness Evaluation of the Multimedia Technology Teachers in Implementing Curriculum 2011 in Timor-Leste - Savio, Leovelgilda Fernandes; Samsudi, Samsudi; Prihatin, Titi (Innovative Journal of Curriculum and Educational Technology, 2020)
The implementation of the Timor-Leste curriculum 2011 for the multimedia technology subject at Public High School in Baucau sub-district needs to be evaluated for maintaining the consistency of the curriculum objective achievements. This research aims to know the teachersÃ¢â‚¬â„¢ readiness in implementing the Timor-Leste curriculum 2011. The aspects considered are official language competence, academic qualification, pedagogical competence, and professional competence. This research is a survey analysis using 7 respondents of multimedia technology teachers. The result of the research shows that the teachers at Public High School 01 and 02 in Baucau Sub-district are in the "highÃ¢â‚¬Â category because the percentage of achievement from the four aspects is 91.71 % until 85%. The teachersÃ¢â‚¬â„¢ readiness should be evaluated as the guidance or resource to increase the teachers' competence from the aspect of academic competence, teachers' qualifications, pedagogical competence, and professional competence to give the qualified output of the education.